Psychometric evaluation of the career decision scale with Iranian undergraduate students - Nasab, Mojgan Fadaei; Abdul Kadir, Rusnani; Hassan, Siti Aishah; Mohd. Noah, Sidek (Wiley-Blackwell Publishing, 2015)
The authors examined the reliability and construct validity of the Career Decision Scale (Osipow, Carney, & Barak, 1976) with 1,610 freshman and sophomore students from public universities from a southwestern state in Iran. A Cronbach's alpha of .80 provided strong support for the scale's reliability. Exploratory factor analysis results indicated a 2-factor model (Diffusion and Internal/External Barriers) of the scale with Iranian students, which was confirmed by confirmatory factor analysis. Implications and recommendations for further research are discussed.